2006
DOI: 10.1002/pssb.200565205
|View full text |Cite
|
Sign up to set email alerts
|

Growth of AlN nanowires by metal organic chemical vapour deposition

Abstract: AlN nanowires with a diameter of 20 nm were grown stochastically by the vapour-liquid-solid (VLS) method. At low temperatures below 1000 °C the Kirkendall effect during the alloying of aluminium and the catalyst resulted in the formation of three-dimensional nanostructures like lamellas and nano flowers. The high temperatures above 1000 °C, which are necessary to grow the nanowires complicate the control of their formation. Small catalyst droplets of 20 nm diameter are not stable due to their evaporation. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…From their observations, the group concluded that the stability of the liquid droplets and the selectivity in the VLS growth process relied very much on the supersaturation level and surface stoichiometry. Apart from the conventional approach of growing a single nanowire out of a liquid droplet, Cimalla et al [42] demonstrated the synthesis of high-density AlN nanowire networks inside larger 3D structures with diameters up to 5 lm. Using both Ni and Au catalysts to facilitate and sustain VLS growth, the group successfully fabricated AlN nanowires with a diameter of roughly 20 nm at temperatures between 900 and 1100°C.…”
Section: Catalyst-assisted Vls Growth Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From their observations, the group concluded that the stability of the liquid droplets and the selectivity in the VLS growth process relied very much on the supersaturation level and surface stoichiometry. Apart from the conventional approach of growing a single nanowire out of a liquid droplet, Cimalla et al [42] demonstrated the synthesis of high-density AlN nanowire networks inside larger 3D structures with diameters up to 5 lm. Using both Ni and Au catalysts to facilitate and sustain VLS growth, the group successfully fabricated AlN nanowires with a diameter of roughly 20 nm at temperatures between 900 and 1100°C.…”
Section: Catalyst-assisted Vls Growth Methodsmentioning
confidence: 99%
“…Various fabrication methods have been employed to synthesize these nanowires and they may be classified into four main classes: (1) template-confined method [16,[31][32][33], (2) direct current (DC) arc discharge method [34][35][36][37][38], (3) catalyst-assisted vapor-liquid-solid (VLS) growth method [39][40][41][42][43][44][45][46], and (4) catalyst-free vapor-solid (VS) growth method [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. Although significant progress in the synthesis of AlN nanowires has been achieved lately, some challenges remain and are expected to be overcome in the near future.…”
Section: Introduction and Background Of Aluminum Nitride (Aln) Nanowiresmentioning
confidence: 99%
“…However, to our knowledge, few AlN nanowires have been synthesized via VLS growth with the clear observations of metallic catalyst particles on the top of nanowires [15]. Although many research groups speculated that as-synthesized AlN nanowires were grown via VLS mechanism, no observations of metallic catalyst particles on the top of nanowires made their claims inconvincible [16][17][18]. Very recently, Hu et al demonstrated the detailed VLS growth process of the sparse AlN nanowires from the nitridation of Al-Ni alloys at the high reaction temperature up to 1100 1C using the bimetallic phase equilibrium diagram [19].…”
Section: Introductionmentioning
confidence: 94%
“…are attracting increasing interest due to their versatile chemical and physical properties. In order to get these advanced semiconductor materials with high yield, many various and novel precursors were used, such as metal powders [1][2][3][4][5][6], metalorganic compounds [7][8][9][10], suboxides usually from the reaction between reducer and metal oxide [11][12][13][14], oxides [15], halides [16][17][18], and the product itself through physical evaporation [19]. Nevertheless, the direct nitridation or oxidation of metals via thermal chemical vapor deposition (CVD) has the advantage of low costs and easy operations due to its cheap raw materials and simple reaction system.…”
Section: Introductionmentioning
confidence: 99%